PERAN MEDIA MASSA DALAM PENANGANAN STUNTING DI JAKARTA - Indriani, Indriani; Hayati, Farida; Ariefaldy, Muhammad Ilhan; Satrio, Rezky Metra (Media Bahasa, Sastra, dan Budaya Wahana, 2024)
Stunting has become a major problem in various developing countries, including Indonesia. A report from the Indonesian Nutrition Status Survey (SSGI) in 2022 stated that the prevalence of stunting in Indonesia was 21.6%. Meanwhile, the prevalence of stunting in DKI Jakarta is 14.8%. Handling stunting cannot only be done through one sector, because stunting is also caused by many factors. In handling stunting, mass communication has an important role in changing people's behavior. The research was conducted using a qualitative method to find out how the process carried out by the mass media in reporting related to stunting handling, especially in DKI Jakarta. From the results of the study, it is known that the issue of stunting has not been considered attractive to the mainstream media and the packaging of news about stunting tends to be monotonous so that it is considered less interesting for the public to read it. Efforts are needed to optimize social media so that the message of stunting prevention and handling can reach the community. Keywords: behavior, handling stunting, media, journalist.